Heat-resistant high-strength aluminum alloy and preparation method thereof
By adding nanoporous boron carbide to the aluminum alloy and penetrating using ultrasonic technology, the problems of reduced strength and insufficient heat resistance at high temperatures are solved, and the effects of high strength and high heat resistance are achieved.
Patent Information
- Application Number
- CN202411370466.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Aluminum alloys are prone to fracture under high temperatures, their strength decreases, and react with other metals, which roughens the crystals and reduces heat resistance.
Aluminum alloy melts were prepared according to the ratio of aluminum and other metals, and infiltrated into nanoporous boron carbide in a melted state using ultrasonic technology to prepare.
Through the addition of nanoporous boron carbide, the strength and heat resistance of the aluminum alloy are significantly improved, impurity corrosion and reaction at high temperatures are reduced, and compound network structures of eutectic silicon and heterogeneous metals are formed.
Smart Images

Figure BDA0005067444010000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and in particular to a heat-resistant high-strength aluminum alloy and a preparation method thereof. Background Art
[0002] As we all know, aluminum alloys have a series of advantages such as low density, light weight, low cost, high specific strength, corrosion resistance, and easy forming, and have been widely used in aviation, aerospace, shipbuilding and other industrial fields. Aluminum alloys are made by adding some alloying elements to pure aluminum, such as Al-Mn alloys made by adding manganese elements to pure aluminum, Al-Cu alloys made by adding copper elements to pure aluminum, Al-Cu-Mg hard aluminum alloys made by adding copper and magnesium elements to pure aluminum, and Al-Zn-Mg-Cu super-hard aluminum alloys made by adding zinc, magnesium and copper elements to pure aluminum.
[0003] However, aluminum alloys are prone to fracture and their strength decreases significantly under high temperature conditions. This is because under high temperature conditions, metal aluminum is easily corroded by impurities in it and reacts with other metals, causing the crystals to coarsen rapidly, which seriously reduces the heat resistance of the alloy. On this basis, adding other rare metals and fillers is a research direction for improving the strength of aluminum alloys; how to make the added metals and aluminum alloys better blended to improve performance, and how to add fillers to avoid the reaction and corrosion of impurities with metal aluminum are the research directions of this invention. Summary of the invention
[0004] The object of the present invention is to provide a heat-resistant high-strength aluminum alloy and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a heat-resistant high-strength aluminum alloy, which is prepared by preparing an aluminum alloy melt by mixing aluminum and other metals in a ratio, assisted by ultrasound, and then infiltrating the melt into nanoporous boron carbide for cold pressing.
[0006] Furthermore, the metal ratio is 0.04% to 0.06% copper, 0.2% to 0.3% magnesium, 0.1% to 0.2% iron, 0.05% to 0.1% silicon, 0.015% to 0.03% erbium, 0.015% to 0.03% titanium, 0.15% to 0.25% zinc, 0.15% to 0.20% manganese, and the balance is aluminum.
[0007] Furthermore, the nanoporous boron carbide is prepared by vacuum sintering to prepare porous boron carbide particles, which are then ball-milled to nanometer level.
[0008] Furthermore, a method for preparing a heat-resistant high-strength aluminum alloy comprises the following preparation steps:
[0009] (1) mixing aluminum and other nano-metal particles according to a ratio, wherein the chemical composition of the aluminum alloy is as follows: 0.04% to 0.06% copper, 0.2% to 0.3% magnesium, 0.1% to 0.2% iron, 0.05% to 0.1% silicon, 0.015% to 0.03% erbium, 0.015% to 0.03% titanium, 0.15% to 0.25% zinc, 0.15% to 0.20% manganese, and the balance is aluminum; placing the billet in a heating furnace and heating it to 540° C. to 580° C., and keeping the temperature for 20 h to 25 h;
[0010] (2) raising the temperature of the heat-treated blank to 1000° C. to 1300° C., maintaining the temperature for 5 to 15 minutes, and introducing ultrasound into the blank for 1 to 10 minutes, with an ultrasonic treatment power of 300 to 500 W and an ultrasonic frequency of 40 kHz;
[0011] (3) Cooling the melt after ultrasonic treatment to 800-1200°C, adding 0.5-3.5% of the melt mass of nanoporous boron carbide particles, evacuating to 0.1 Pa and then filling with inert gas for protection, then heating to 900-1300°C and keeping it warm for 0.5-2.5h; after the end of the insulation, cooling it at a cooling rate of 80-100°C / s; transferring the cooled composite aluminum alloy block to a 3600T hydraulic press, and cold pressing it through a uniform height block until one round of cold pressing is completed; heating the aluminum alloy block to 300-500°C, then water cooling it, and after cooling it to room temperature, performing a second stage of cold pressing, after which the aluminum alloy block is deformed by 1.5-3.5% in each region along the height direction to produce a heat-resistant high-strength aluminum alloy.
[0012] Furthermore, the preparation method of the nanoporous boron carbide in step (3) is to ball mill the porous boron carbide, with a ball-to-material ratio of 1:10, the medium being an iron ball with a diameter of 50 mm, and the grinding time being 2 h.
[0013] Furthermore, the particle size of the nanoporous boron carbide is 60 nm.
[0014] Furthermore, the porous boron carbide preparation method is to add polyvinyl alcohol 0.3 times the mass of boron carbide to boron carbide powder, cold press molding at 40MPa, and heat the prepared cold pressed boron carbide block to 1750-1950°C and perform pressureless vacuum sintering for 10 minutes to prepare porous boron carbide. When the boron carbide block is heated to 500°C, it is kept warm for 1 hour to increase the porosity.
[0015] Furthermore, when the temperature of the boron carbide block is raised to 500° C., the temperature is maintained for 1 hour to increase the porosity.
[0016] Furthermore, the inert gas in step (3) is argon.
[0017] Furthermore, in step (3), the amount of argon introduced is 0.5 L / min.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The present invention prepares aluminum alloy melt according to a proportion of aluminum and other metals with the aid of ultrasound, and then infiltrates into nano porous boron carbide in a molten state to prepare a composite aluminum alloy by cold pressing to achieve high strength and high heat resistance.
[0020] First, erbium metal, titanium metal and other metal raw materials of aluminum alloy are mixed, and then smelted at high temperature. After heat treatment, erbium and titanium will form a double-layer nano-precipitation phase. The metal melt is homogenized by ultrasound, so that the nano-precipitation phase is dispersed in the solution. The fineness of the metal particle crystals formed in the aluminum alloy is further improved by controlling the cooling rate, thereby improving its performance. When the aluminum alloy is used, the aluminum crystals of the titanium metal on the outer layer of the nano-precipitation phase are eroded by other impurities due to the high temperature, thereby reducing the carbon element in the porous boron carbide added later and the aluminum element reacting at high temperature to form aluminum carbide. At the same time, the metastable phase in the alloy can form a complex strengthening phase with the nano-precipitation phase at high temperature, thereby reducing the high temperature so that the metastable phase is transformed, thereby weakening the high temperature resistance of the alloy. On this basis, eutectic silicon and multi-phase metal form a compound network structure, which significantly improves the heat resistance of the alloy.
[0021] Secondly, porous boron carbide particles are prepared by vacuum sintering and ground to the nanometer level. Then, the porous boron carbide particles are added to the aluminum alloy melt. The boron element reacts with the impurity elements in the alloy to boride, and the impurity element content is reduced. The grains can be refined to form fine dispersed precipitates. This dispersed phase hinders the growth of the grains, thereby significantly increasing the recrystallization temperature, significantly improving the strength and elongation of the alloy, and making the alloy have higher heat resistance. The molten metal liquid is infiltrated into the porous boron carbide particles by the infiltration method, and then the alloy is subjected to high pressure through two-stage cold pressing to discharge the gas in the alloy, and the various components are more closely combined, thereby further improving its strength and density, and making it have excellent mechanical properties. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] (1) Aluminum and other nano-metal particles are mixed in a ratio, wherein the chemical composition of the aluminum alloy is as follows: 0.04% copper, 0.2% magnesium, 0.1% iron, 0.05% silicon, 0.015% erbium, 0.015% titanium, 0.15% zinc, 0.15% manganese, and the balance is aluminum; the blank is placed in a heating furnace and heated to 540° C., and kept at this temperature for 20 hours;
[0025] (2) raising the temperature of the heat-treated blank to 1000°C, keeping the temperature for 5 minutes, and introducing ultrasound into the blank for 1 minute. The ultrasonic treatment power is 300 W and the ultrasonic frequency is 40 kHz.
[0026] (3) Adding 0.3 times the mass of polyvinyl alcohol to the boron carbide powder, cold pressing at 40 MPa, heating the prepared cold pressed boron carbide block to 500°C, keeping the temperature for 1 hour to increase the porosity, and then heating it to 1750°C and sintering it in a pressureless vacuum for 10 minutes to prepare porous boron carbide; ball milling the porous boron carbide with a ball-to-material ratio of 1:10, an iron ball with a diameter of 50 mm, and a grinding time of 2 hours to obtain a nanoporous boron carbide with a particle size of 60 nm; cooling the melt after ultrasonication to 800°C, adding a melt mass of 0 .5% nano porous boron carbide particles are evacuated to 0.1Pa and then filled with argon gas at a flow rate of 0.5L / min for protection, and then the temperature is raised to 900℃ and kept warm for 0.5h; after the insulation is completed, it is cooled at a cooling rate of 80℃ / s; the cooled composite aluminum alloy block is transferred to a 3600T hydraulic press and cold pressed through an isohelite block until one circle of cold pressing is completed; the aluminum alloy block is heated to 300℃, then water-cooled, and then cooled to room temperature for two-stage cold pressing. After the end, the aluminum alloy block is deformed by 1.5% in each area along the height direction to make a heat-resistant and high-strength aluminum alloy.
[0027] Example 2
[0028] (1) Aluminum and other nano-metal particles are mixed in a ratio, wherein the chemical composition of the aluminum alloy is as follows: 0.05% copper, 0.25% magnesium, 0.15% iron, 0.725% silicon, 0.0225% erbium, 0.0225% titanium, 0.2% zinc, 0.175% manganese, and the balance is aluminum; the blank is placed in a heating furnace and heated to 560° C., and kept warm for 22 hours;
[0029] (2) raising the temperature of the heat-treated blank to 1150°C, keeping the temperature for 10 min, and introducing ultrasound into the blank for 5 min. The ultrasonic treatment power is 400 W and the ultrasonic frequency is 40 kHz.
[0030] (3) Adding 0.3 times the mass of polyvinyl alcohol to the boron carbide powder, cold pressing at 40 MPa, heating the prepared cold pressed boron carbide block to 500°C, keeping the temperature for 1 hour to increase the porosity, and then heating it to 1850°C and sintering it in a pressureless vacuum for 10 minutes to prepare porous boron carbide; ball milling the porous boron carbide, with a ball-to-material ratio of 1:10, an iron ball as the medium, a diameter of the iron ball of 50 mm, and a grinding time of 2 hours, to obtain a nanoporous boron carbide with a particle size of 60 nm; cooling the melt after ultrasonication to 1000°C, adding 2% by mass of the melt The nanoporous boron carbide particles are evacuated to 0.1Pa and then filled with argon gas with a flow rate of 0.5L / min for protection, and then the temperature is raised to 1100℃ and kept warm for 1.5h; after the insulation is completed, it is cooled at a cooling rate of 80-100℃ / s; the cooled composite aluminum alloy block is transferred to a 3600T hydraulic press and cold pressed through an isohyper block until one circle of cold pressing is completed; the aluminum alloy block is heated to 400℃, then water-cooled, and then cooled to room temperature for two-stage cold pressing. After the end, the aluminum alloy block is deformed by 2.5% in each region along the height direction to make a heat-resistant and high-strength aluminum alloy.
[0031] Example 3
[0032] (1) Aluminum and other nano-metal particles are mixed in a ratio, wherein the chemical composition of the aluminum alloy is as follows: 0.06% copper, 0.3% magnesium, 0.2% iron, 0.1% silicon, 0.03% erbium, 0.03% titanium, 0.25% zinc, 0.20% manganese, and the balance is aluminum; the blank is placed in a heating furnace and heated to 580° C., and kept at this temperature for 25 hours;
[0033] (2) raising the temperature of the heat-treated blank to 1300°C, keeping the temperature for 15 minutes, and introducing ultrasound into the blank for 10 minutes. The ultrasonic treatment power is 500 W and the ultrasonic frequency is 40 kHz.
[0034] (3) Adding 0.3 times the mass of polyvinyl alcohol to the boron carbide powder, cold pressing at 40 MPa, heating the prepared cold pressed boron carbide block to 500°C, keeping the temperature for 1 hour to increase the porosity, and then heating it to 1950°C and sintering it in a pressureless vacuum for 10 minutes to prepare porous boron carbide; ball milling the porous boron carbide with a ball-to-material ratio of 1:10, an iron ball with a diameter of 50 mm, and a grinding time of 2 hours to obtain a nanoporous boron carbide with a particle size of 60 nm; cooling the melt after ultrasonication to 1200°C, adding 3 .5% nano porous boron carbide particles are evacuated to 0.1Pa and then filled with argon gas at a flow rate of 0.5L / min for protection, and then the temperature is raised to 1300℃ and kept warm for 2.5h; after the insulation is completed, it is cooled at a cooling rate of 100℃ / s; the cooled composite aluminum alloy block is transferred to a 3600T hydraulic press and cold pressed through an isohelite block until one circle of cold pressing is completed; the aluminum alloy block is heated to 500℃, then water-cooled, and then cooled to room temperature for two-stage cold pressing. After the end, the aluminum alloy block is deformed by 3.5% in each area along the height direction to make a heat-resistant and high-strength aluminum alloy.
[0035] Comparative Example 1
[0036] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: aluminum and other nano-metal particles are mixed according to a ratio, and the chemical composition weight percentage of the aluminum alloy is: copper is 0.05%, magnesium is 0.25%, iron is 0.15%, silicon is 0.725%, zinc is 0.2%, manganese is 0.175%, and the balance is aluminum; the blank is placed in a heating furnace and heated to 560°C and kept warm for 22 hours; the remaining steps are the same as Example 2.
[0037] Comparative Example 2
[0038] The difference between Comparative Example 2 and Example 2 lies in the difference in steps (2) and (3). Steps (2) and (3) are changed to: (2) raising the temperature of the heat-treated blank to 1150° C. and keeping the temperature for 10 min;
[0039] (3) Adding 0.3 times the mass of polyvinyl alcohol to the boron carbide powder, cold pressing at 40 MPa, heating the prepared cold pressed boron carbide block to 500°C, keeping the temperature for 1 hour to increase the porosity, and then heating it to 1850°C and sintering it in a pressureless vacuum for 10 minutes to prepare porous boron carbide; ball milling the porous boron carbide with a ball-to-material ratio of 1:10, an iron ball with a diameter of 50 mm, and a grinding time of 2 hours to obtain nanoporous boron carbide with a particle size of 60 nm; cooling the melt treated at high temperature to 1000°C, adding 2% of the melt mass of nanoporous boron carbide The porous boron carbide particles are evacuated to 0.1Pa and then filled with argon gas with a flow rate of 0.5L / min for protection, and then the temperature is raised to 1100°C and kept warm for 1.5h; after the insulation is completed, it is cooled at a cooling rate of 80-100°C / s; the cooled composite aluminum alloy block is transferred to a 3600T hydraulic press and cold pressed through an isohyper block until one circle of cold pressing is completed; the aluminum alloy block is heated to 400°C, then water-cooled, and after cooling to room temperature, a second stage of cold pressing is performed, and after the end, the aluminum alloy block is deformed by 2.5% in each region along the height direction to form a heat-resistant high-strength aluminum alloy; the remaining steps are the same as in Example 2.
[0040] Comparative Example 3
[0041] The difference between Comparative Example 3 and Example 2 lies in the difference in step (3), where step (3) is modified as follows: cooling the melt after ultrasound to 1000°C, evacuating to 0.1 Pa, and then filling with argon gas at a flow rate of 0.5 L / min for protection, then heating to 1100°C and keeping warm for 1.5 hours; after the insulation is completed, cooling it at a cooling rate of 80 to 100°C / s; transferring the cooled composite aluminum alloy block to a 3600T hydraulic press, and cold pressing it through an iso-block until one round of cold pressing is completed; heating the aluminum alloy block to 400°C, then water-cooling it, and after cooling it to room temperature, performing two-stage cold pressing, after which the aluminum alloy block is deformed by 2.5% in each region along the height direction to form a heat-resistant high-strength aluminum alloy; the remaining steps are the same as Example 2.
[0042] Comparative Example 4
[0043] The difference between Comparative Example 4 and Example 2 is that step (2) is different, and step (3) is changed to: boron carbide is ball-milled, the ball-to-material ratio is 1:10, the medium is an iron ball, the diameter of the iron ball is 50 mm, the grinding time is 2 h, and the particle size of the obtained nano-boron carbide is 60 nm; the melt after ultrasound is cooled to 1000 ° C, 2% of the mass of nano-boron carbide particles of the melt is added, and evacuated to 0.1 Pa and then filled with argon gas with a flow rate of 0.5 L / min for protection, and then The temperature was raised to 1100°C and kept warm for 1.5 hours; after the insulation was completed, the block was cooled at a cooling rate of 80-100°C / s; the cooled composite aluminum alloy block was transferred to a 3600T hydraulic press and cold pressed through an isohyper block until one round of cold pressing was completed; the aluminum alloy block was heated to 400°C, water-cooled, and cold pressed in two stages after cooling to room temperature. After the cold pressing was completed, the aluminum alloy block was deformed by 2.5% in each region along the height direction to produce a heat-resistant high-strength aluminum alloy; the remaining steps were the same as those in Example 2.
[0044] Comparative Example 5
[0045] The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: add polyvinyl alcohol 0.3 times the mass of boron carbide to the boron carbide powder, cold press the prepared cold pressed boron carbide block at 40 MPa, heat it to 500 ° C, keep it warm for 1 hour to increase the porosity, and then heat it to 1850 ° C and sinter it in a pressureless vacuum for 10 minutes to prepare porous boron carbide; ball mill the porous boron carbide with a ball-to-material ratio of 1:10, the medium is an iron ball, and the diameter of the iron ball is 5 0mm, the grinding time is 2h, and the particle size of the obtained nanoporous boron carbide is 60nm; the melt after ultrasound is cooled to 1000℃, 2% of the melt mass of nanoporous boron carbide particles are added, and evacuated to 0.1Pa and then filled with argon with a flow rate of 0.5L / min for protection, and then heated to 1100℃ and kept warm for 1.5h; after the insulation is completed, it is cooled at a cooling rate of 80-100℃ / s, and the heat-resistant high-strength aluminum alloy is prepared after cooling; the remaining steps are the same as those in Example 2.
[0046] Effect example
[0047] Table 1 below shows the performance analysis results of a heat-resistant high-strength aluminum alloy using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0048] Table 1
[0049]
[0050] From the comparison of the experimental data of the mechanical properties of the embodiment and the comparative example, it can be found that the present invention mixes metal erbium with metal titanium and other metal raw materials of aluminum alloy, and then performs high-temperature smelting. After heat treatment, erbium and titanium will form a nano-precipitation phase with a double-layer structure, and the metal melt is uniformly dispersed in the solution by ultrasound, and the fineness of the metal particle crystal formation in the aluminum alloy is further improved by controlling the cooling rate, thereby improving its performance. The present invention infiltrates the molten metal liquid into the porous boron carbide particles by the infiltration method, and then the alloy is subjected to high pressure through two-stage cold pressing to discharge the gas in the alloy, and the various components are more closely combined, thereby further improving its strength and density, so that it has excellent mechanical properties. From the comparison of the experimental data of the performance after high temperature treatment of the embodiment and the comparative example, it can be found that the metal titanium of the outer layer of the nano-precipitation phase generated by the present invention can reduce the aluminum crystals caused by high temperature being eroded by other impurities when the aluminum alloy is used, reduce the carbon element in the porous boron carbide added later and the aluminum element reacting at high temperature to form aluminum carbide, and at the same time, the metastable phase in the alloy can form a complex strengthening phase with the nano-precipitation phase at high temperature, reduce the high temperature so that the metastable phase is transformed, thereby weakening the high temperature resistance of the alloy, and on this basis, eutectic silicon and multiphase metal are formed to form a compound network structure, which significantly improves the heat resistance of the alloy. The porous boron carbide particles are prepared by vacuum sintering, ground to nanometer level, and then the porous boron carbide particles are added to the aluminum alloy melt, the boron element reacts with the impurity elements in the alloy, the impurity element content is reduced, and the grains can be refined to form fine dispersed precipitation phases, which hinder the growth of the grains, thereby significantly increasing the recrystallization temperature, significantly improving the strength and elongation of the alloy, and making the alloy have higher heat resistance.
[0051] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A heat-resistant high-strength aluminum alloy, characterized in that: The aluminum alloy is prepared by preparing an aluminum alloy melt by mixing aluminum and other metals in a certain ratio, and then infiltrating the melt into nano porous boron carbide and cold pressing the melt to form the aluminum alloy.
2. The heat-resistant high-strength aluminum alloy according to claim 1, characterized in that: The metal ratio is 0.04%-0.06% copper, 0.2%-0.3% magnesium, 0.1%-0.2% iron, 0.05%-0.1% silicon, 0.015%-0.03% erbium, 0.015%-0.03% titanium, 0.15%-0.25% zinc, 0.15%-0.20% manganese, and the balance is aluminum.
3. The heat-resistant high-strength aluminum alloy according to claim 2, characterized in that: The nano porous boron carbide is prepared by vacuum sintering to prepare porous boron carbide particles, which are ball-milled to nanometer level.
4. A method for preparing a heat-resistant high-strength aluminum alloy, characterized in that: The method comprises the following preparation steps: (1) mixing aluminum and other nano-metal particles according to a ratio, wherein the chemical composition of the aluminum alloy is as follows: 0.04% to 0.06% copper, 0.2% to 0.3% magnesium, 0.1% to 0.2% iron, 0.05% to 0.1% silicon, 0.015% to 0.03% erbium, 0.015% to 0.03% titanium, 0.15% to 0.25% zinc, 0.15% to 0.20% manganese, and the balance is aluminum; placing the billet in a heating furnace and heating it to 540° C. to 580° C., and keeping the temperature for 20 h to 25 h; (2) raising the temperature of the heat-treated blank to 1000° C. to 1300° C., maintaining the temperature for 5 to 15 minutes, and introducing ultrasound into the blank for 1 to 10 minutes, with an ultrasonic treatment power of 300 to 500 W and an ultrasonic frequency of 40 kHz; (3) Cooling the melt after ultrasonic treatment to 800-1200°C, adding 0.5-3.5% of the melt mass of nanoporous boron carbide particles, evacuating to 0.1 Pa and then filling with inert gas for protection, then heating to 900-1300°C and keeping it warm for 0.5-2.5h; after the end of the insulation, cooling it at a cooling rate of 80-100°C / s; transferring the cooled composite aluminum alloy block to a 3600T hydraulic press, and cold pressing it through a uniform height block until one round of cold pressing is completed; heating the aluminum alloy block to 300-500°C, then water cooling it, and after cooling it to room temperature, performing a second stage of cold pressing, after which the aluminum alloy block is deformed by 1.5-3.5% in each region along the height direction to produce a heat-resistant high-strength aluminum alloy.
5. The method for preparing a heat-resistant high-strength aluminum alloy according to claim 4, characterized in that: The preparation method of the nanoporous boron carbide in step (3) is to ball mill the porous boron carbide, with a ball-to-material ratio of 1:10, an iron ball as the medium, a diameter of the iron ball of 50 mm, and a grinding time of 2 hours.
6. The method for preparing a heat-resistant high-strength aluminum alloy according to claim 5, characterized in that: The particle size of the nanoporous boron carbide is 60 nm.
7. The method for preparing a heat-resistant high-strength aluminum alloy according to claim 5, characterized in that: The porous boron carbide preparation method comprises adding polyvinyl alcohol 0.3 times the mass of boron carbide to boron carbide powder, cold pressing at 40MPa, heating the prepared cold pressed boron carbide block to 1750-1950°C and performing pressureless vacuum sintering for 10 minutes to prepare porous boron carbide. When the boron carbide block is heated to 500°C, it is kept warm for 1 hour to increase the porosity.
8. The method for preparing a heat-resistant high-strength aluminum alloy according to claim 7, characterized in that: When the temperature of the boron carbide block is raised to 500° C., the temperature is maintained for 1 hour to increase the porosity.
9. The method for preparing a heat-resistant high-strength aluminum alloy according to claim 4, characterized in that: The inert gas in step (3) is argon.
10. The method for preparing a heat-resistant high-strength aluminum alloy according to claim 4, characterized in that: The amount of argon introduced in step (3) is 0.5 L / min.
Citation Information
Patent Citations
Preparation method of B4C / Al composite material
CN103643060A
Method for preparing B4C / Al neutron absorber material panel through continuous roll-casting
CN103789599A
High-strength aluminum alloy material special for automobile lamps and preparation method of aluminum alloy material
CN111534727A
Boron carbide-containing aluminum composite material and method for producing the same
JP2011074444A
Method of preparing boron carbide / aluminum cermets having a controlled microstructure
US5394929A